2021
DOI: 10.1371/journal.pone.0248041
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection rates in dyspeptic Serbian HIV-infected patients compared to HIV-negative controls

Abstract: Helicobacter pylori infection does not belong to the spectrum of opportunistic infections in people living with HIV (PLHIV). To evaluate the Helicobacter pylori infection prevalence rate trends in HIV co-infected individuals in comparison to the HIV-negative population, we compared histopathological findings of H. pylori positive gastritis (gastritis topography and histopathology) between 303 PLHIV and 2642 HIV-negative patients who underwent esophagogastroduodenoscopy (EGD) between 1993 and 2014 due to dyspep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…pylori infection is often considered a disease of poverty as it is associated with poor hygiene and sanitation conditions and is more prevalent in low-income and developing countries where HIV infection is rampant. We found that H. pylori infection rate was higher in HIV-positive patients compared to HIV-negative controls although several other studies reported a lower H. pylori infection prevalence in HIV-positive patients than HIV-negative individuals [11][12][13][14]. The present study investigated the effect of H. pylori infection on CD4 + T cell counts and HIV viral load levels, which are the most important and widely used predictors of progression to AIDS [22], among people infected with HIV in a high co-endemic setting.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…pylori infection is often considered a disease of poverty as it is associated with poor hygiene and sanitation conditions and is more prevalent in low-income and developing countries where HIV infection is rampant. We found that H. pylori infection rate was higher in HIV-positive patients compared to HIV-negative controls although several other studies reported a lower H. pylori infection prevalence in HIV-positive patients than HIV-negative individuals [11][12][13][14]. The present study investigated the effect of H. pylori infection on CD4 + T cell counts and HIV viral load levels, which are the most important and widely used predictors of progression to AIDS [22], among people infected with HIV in a high co-endemic setting.…”
Section: Discussionmentioning
confidence: 52%
“…pylori co-infections may affect the course of HIV disease progression. H. pylori infection is common in HIV-positive patients, especially in developing countries where both infections are prevalent, although there are conflicting findings on the prevalence of H. pylori infection in HIVpositive patients compared to HIV-negative individuals [11][12][13][14][15][16][17]. H. pylori is a bacterium that can colonize the lining of the gastric and duodenal mucosa and has been associated with a range of gastrointestinal diseases, including gastritis and ulcers [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous reports using either H. felis or H. pylori have demonstrated that immunodeficient SCID mice had increased colonization compared to WT mice ( Blanchard et al, 1995 ; Eaton et al, 1999 ; Nedrud et al, 2012 ). Additionally, no difference in bacterial load has been observed in HIV positive and negative patients despite the significance differences in host immune response ( Spurnic et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Radovanovic Spurnic et al (2021) the prevalence of Helicobacter pylori infection in Central Serbia was significantly higher in HIV-negative controls than in in people living with HIV (50.2% vs. 28.1%). The prevalence of Helicobacter pylori infection in Central Serbia is still unknown [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic Helicobacter pylori infection is a significant risk factor and increases the risk for developing stomach cancer within ten years of infection 5.9 times [ 16 ]. There are no available data for Helicobacter pylori chronic infection prevalence in the Republic of Serbia [ 17 ].…”
Section: Introductionmentioning
confidence: 99%